A performance of fermented soybean in water treatment - Muhammad Aiman Fikri, Mohamad Azlan (2019)
The river has many important uses, it is very important for its quality to be monitored and reviewed continuously. If the river is not maintained, many adverse effects will occur in the future such as river pollution. River pollution affects river ecosystems and also causes poor water quality. Steps to treat river water should be taken so that the river's water quality will always be clean. Therefore, the objective of this study is to determine the River Belat Water Quality Index (WQI) based on the six parameters in the WQI scope, to classify the Belat River based on WQI which has been determined and to compare WQI in Belat River with and to see the effectiveness of river water treatment methods using fermented soy powder. Fermented soybean will acts a coagulant for the process of flocculation. Flocculation will stick all the residue or sediment in the sample. And after that, the sample with be filter in order to remove the dirt. Next, testing for Water Quality Index will be done. Based on the results of the study, the value of WQI for the Belat River is 79. This value is obtained after taking into account the sub-index of the six parameters of WQI ie Dilute Oxygen (DO), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Suspended Solids (TSS), Ammonia Nitrogen (AN) and pH. For the determination of the Belat River classification, the WQI value has been shown to indicate the Belat River is below Class III. The water quality of Belat River recovered with fermented soybean powder is better now where the WQI value is 91.7 and is below Class II, slightly to Class I.